From Splendid Isolation to Global Engagement Exploring Internationalization in Higher Education - Wolf, Birgit; Schmohl, Tobias (wbv Media, 2023)
This publication aspires to clarify and illustrate the role of higher education in promoting internationalisation, especially Internationalization at Home (IaH). It aims to highlight higher education's three central roles: teaching, research, and community service, each in its global context. The anthology actively promotes change and development in the higher education sector and identifies strategies like online learning platforms and community partnerships that make higher education more accessible and enhance its benefits. The publication comprises two interconnected sections: the first addresses the evolving classroom dynamics due to IaH, focusing on curriculum adaptations for a varied student body. The second section delves into educational goals, emphasizing an international perspective. Targeted at educators and researchers, the anthology offers guidance on integrating international and intercultural perspectives into curricula and teaching methods, with a focus on social inclusivity.